E-SERVICE DALAM PENYALURAN INSENTIF USAHA MIKRO, KECIL, DAN MENENGAH (BANTUAN BAGI PELAKU USAHA MIKRO TAHAP 3) TAHUN 2021 DI KABUPATEN DEMAK - Bilhaq, Eqtadha -; erowati, dewi -; astuti, puji - (Journal of Politic and Government Studies, 2025)
The Covid-19 pandemic has encouraged the government to strive for economic improvement and the development of electronic services, while the quality of qualified services will improve people's welfare. E-Service in the distribution of Assistance for Micro Business Actors (BPUM) Phase 3 of 2021 by Dinas Perdagangan Koperasi dan UKM Kabupaten Demak as a form of technological advancement and reducing physical contact during the pandemic. The discussion of E-Service in the implementation of the programme is aimed at looking at the implementation of services in depth, especially in the distribution of incentives to micro business actors and factors that affect the failure of E-Service. In this study, the method used is a qualitative descriptive method, using observation techniques, interviews, and documentation studies. Data is collected through direct observation of service instruments, interviews with users and officers, and studies of relevant regulations that are referenced in the service.The results of the study show that Dinas Perdagangan Koperasi dan UKM Kabupaten Demak has failed to provide qualified public service quality through electronic services. It was found that the service implementation did not meet most of the components of the E-Service. Various problems in the service such as website inconsistencies and lack of responsiveness pose many obstacles for prospective BPUM recipients in completing the registration process. The lack of resources owned by Dindagkop UKM also causes many other problems such as overworked officers, to user data leaks. Based on the author's findings, Dinas Perdagangan Koperasi dan UKM Kabupaten Demak should improve and enhance the quality of electronic services by optimising and automating services as well as revamping service strategies as a whole